2021
DOI: 10.3390/ijms22073302
|View full text |Cite
|
Sign up to set email alerts
|

Engaging the Innate and Adaptive Antitumor Immune Response in Lymphoma

Abstract: Immunotherapy has emerged as a powerful therapeutic strategy for many malignancies, including lymphoma. As in solid tumors, early clinical trials have revealed that immunotherapy is not equally efficacious across all lymphoma subtypes. For example, immune checkpoint inhibition has a higher overall response rate and leads to more durable outcomes in Hodgkin lymphomas compared to non-Hodgkin lymphomas. These observations, combined with a growing understanding of tumor biology, have implicated the tumor microenvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 305 publications
0
6
0
Order By: Relevance
“…As naïve B cell clones are less sensitive to Rituximab treatment due to their lower expression of CD20, a robust immune response can also be assumed for those patients. Immunosuppressive therapy as well as the lymphoma disease itself may have diminished the T cellular axis of immune defence against SARS-CoV-2, which targets infected cells, and loss of control by cytotoxic T cells may have caused the ongoing replication of SARS-CoV-2 in naso-pharyngeal epithelial cells (61, 62). Impaired T cell help may have contributed to the inefficient antibody maturation.…”
Section: Discussionmentioning
confidence: 99%
“…As naïve B cell clones are less sensitive to Rituximab treatment due to their lower expression of CD20, a robust immune response can also be assumed for those patients. Immunosuppressive therapy as well as the lymphoma disease itself may have diminished the T cellular axis of immune defence against SARS-CoV-2, which targets infected cells, and loss of control by cytotoxic T cells may have caused the ongoing replication of SARS-CoV-2 in naso-pharyngeal epithelial cells (61, 62). Impaired T cell help may have contributed to the inefficient antibody maturation.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequently performed ultrasound-guided core biopsy was inconclusive, which may occur in roughly 8% as compared with about 3% in the case of an excisional biopsy ( 19 ). Thus, surgery of the 18 F-FDG-PET-positive liver residual appeared to be the best option to receive reliable histopathology results to guide further treatment decisions ( 20 , 21 ). In case of persistent DLBCL CAR T-cell therapy in patients with primary refractory disease after at least two lines of therapy would have been an option ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…As known to all, immunotherapy has been regarded as a powerful therapeutic strategy for various malignancies, including lymphoma. Failures of lymphoma immunotherapy may come from these mechanisms containing loss of major histocompatibility complexes, expression of immunosuppressive ligands, secretion of immunosuppressive cytokines, and the recruitment, expansion, and skewing of suppressive cell populations ( Csizmar and Ansell, 2021 ). Previous studies have demonstrated that chemotactic responses play an important role in EBV-positive lymphoma processes, such as tumor vasculature development, cancer metastases and apoptosis ( Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%